Polybenzimidazolium hydroxides - Structure, stability and degradation - Henkensmeier, Dirk; Cho, Hyeong-Rae; Kim, Hyoung-Juhn; Kirchner, Carolina Nunes; Leppin, Janine; Dyck, Alexander; Jang, Jong Hyun; Cho, EunAe; Nam, Suk-Woo; Lim, Tae-Hoon (ELSEVIER SCI LTD, 2012)
Polybenzimidazolium hydroxides are of potential interest for the use in alkaline anion exchange membrane fuel cells (AAEMFC). Introduction of an ether group in para-position of the 2-phenyl substituent improves the mesomeric stabilization of imidazolium cations, and O-PBI seems to be more stable than meta-PBI under alkaline conditions. NMR, IR and XPS analysis show a structural change when the iodide form is exchanged into the hydroxide form. Surprisingly, this structural change is subject to a pH sensitive equilibrium and the pure imidazolium form is retained immediately when the pH is lowered. The molecular structure at high pH is either the 2-carbinol or the amine-amide. Further hydrolysis necessitates excess hydroxide. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: EXCHANGE MEMBRANE; FUEL-CELLS; IONOMER